2014
DOI: 10.1007/s10620-014-3126-2
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Dyskinesia and Symptomatic Gallstone Disease in Children: Two Sides of the Same Coin?

Abstract: Background Despite lack of consensus criteria, biliary dyskinesia (BD) is an increasingly accepted pediatric diagnosis. Aims We compared patient characteristics, outcomes, and resource utilization (before and after surgery) between children with BD and symptomatic cholecystolithiasis (LITH). Methods Data from the electronic medical record were abstracted for children diagnosed with BD or LITH between December 1, 2002, and November 30, 2012, at Children’s Hospital of Pittsburgh. Results Four hundred and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 64 publications
1
39
0
1
Order By: Relevance
“…Srinath et al [29] showed that pediatric patients with biliary dyskinesia who underwent cholecystectomy visited gastroenterology clinics more commonly and had more gastrointestinal symptom related hospitalizations than those with symptomatic cholecystolithiasis (OR 7.76, 95% CI 3.58-16.84). They insisted on treatment strategy used for other functional disorder rather than surgical approach, but the use of hepatobiliary scintigraphy is particularly of concern as it involves administration of radiopharmaceuticals to very young patients, infants, and neonates, who are at high potential risk of detrimental effects from ionizing radiation [30].…”
Section: Discussionmentioning
confidence: 99%
“…Srinath et al [29] showed that pediatric patients with biliary dyskinesia who underwent cholecystectomy visited gastroenterology clinics more commonly and had more gastrointestinal symptom related hospitalizations than those with symptomatic cholecystolithiasis (OR 7.76, 95% CI 3.58-16.84). They insisted on treatment strategy used for other functional disorder rather than surgical approach, but the use of hepatobiliary scintigraphy is particularly of concern as it involves administration of radiopharmaceuticals to very young patients, infants, and neonates, who are at high potential risk of detrimental effects from ionizing radiation [30].…”
Section: Discussionmentioning
confidence: 99%
“…While mostly retrospective surgical reports suggest impressive success rates [119], a longitudinal cohort study demonstrated a similar rate of symptom resolution during conservative therapy in more than 80 % of patients with presumed biliary pain but no gallstones, comparable to the improvement described after surgery for symptomatic gallbladder disease [120]. Importantly, resource utilization continues to be high after cholecystectomy for biliary dyskinesia, adding more contemporary support to the cautionary notes of early investigators [7,121].…”
Section: Post-cholecystectomy Syndromementioning
confidence: 95%
“…Postoperative outcomes were consistently worse compared to patients with symptomatic cholelithiasis [33,59,82,107,117,118]. Despite these concerning findings, operations for biliary dyskinesia, defined by a normal appearing gallbladder without stones, have been on the rise and account for up to 20 % of cholecystectomies in adults and even close to 50 % in children [7,8]. While mostly retrospective surgical reports suggest impressive success rates [119], a longitudinal cohort study demonstrated a similar rate of symptom resolution during conservative therapy in more than 80 % of patients with presumed biliary pain but no gallstones, comparable to the improvement described after surgery for symptomatic gallbladder disease [120].…”
Section: Post-cholecystectomy Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Once biliary dyskinesia is diagnosed, the usual treatment is cholecystectomy as there is no accepted medical treatment specific to altering gallbladder function (2,3). The rates of cholecystectomy for pediatric biliary dyskinesia continue to rise in the United States as numerous papers report positive outcomes with little to no surgical complications (4)(5)(6)(7)(8)(9)(10). Biliary dyskinesia is now among the most common conditions resulting in cholecystectomy in children and adolescents (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%